2008
DOI: 10.1128/jvi.02570-07
|View full text |Cite
|
Sign up to set email alerts
|

Murine Cytomegalovirus m38.5 Protein Inhibits Bax-Mediated Cell Death

Abstract: Many viruses encode proteins that inhibit the induction of programmed cell death at the mitochondrial checkpoint. Murine cytomegalovirus (MCMV) encodes the m38.5 protein, which localizes to mitochondria and protects human HeLa cells and fibroblasts from apoptosis triggered by proteasome inhibitors but not from Fas-induced apoptosis. However, the ability of this protein to suppress the apoptosis of murine cells and its role during MCMV infection have not been investigated previously. Here we show that m38.5 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 48 publications
1
49
0
Order By: Relevance
“…20,21,23 We further showed that Bax-knockout cells infected with an m38.5-deficient MCMV mutant (Dm38.5) were resistant to STS-induced apoptosis, suggesting that Bak-mediated apoptosis was inhibited by a different MCMV protein. 20 To test whether m41.1 inhibits apoptosis in a Bak-specific manner, we infected fibroblasts deficient for Bax, Bak, or both proteins with different MCMV mutants and analyzed their sensitivity to STS. For comparison, we also included the previously described Dm38.5 mutant and constructed a double-knockout (dko) mutant lacking both m41.1 and m38.5.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…20,21,23 We further showed that Bax-knockout cells infected with an m38.5-deficient MCMV mutant (Dm38.5) were resistant to STS-induced apoptosis, suggesting that Bak-mediated apoptosis was inhibited by a different MCMV protein. 20 To test whether m41.1 inhibits apoptosis in a Bak-specific manner, we infected fibroblasts deficient for Bax, Bak, or both proteins with different MCMV mutants and analyzed their sensitivity to STS. For comparison, we also included the previously described Dm38.5 mutant and constructed a double-knockout (dko) mutant lacking both m41.1 and m38.5.…”
Section: Resultsmentioning
confidence: 86%
“…23 Moreover, the observation that MCMV-infected cells are protected from Bax-and Bakmediated apoptosis suggested that the virus encodes an additional, Bak-specific antiapoptotic protein. 20 In the present study, we identified the product of MCMV ORF m41.1 as a Bak-specific inhibitor of apoptosis. The m41.1 protein localizes to mitochondria and prevents Bak oligomerization, cyt c release, and execution of PCD.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…They include myxoma virus-encoded M11L (19,20,25), human cytomegalovirus-encoded vMIA (24), murine cytomegalovirus-encoded m38 (38), and vaccinia virus-encoded F1L (21,48,49,61,63) and N1L (2,7,12). Despite the lack of sequence similarity to the Bcl-2 protein family, both F1L and M11L adopt a Bcl-2 fold (16,40,42), and the structure of M11L in complex with the BH3 peptide from Bak revealed that M11L binds BH3 ligands via the canonical BH3 binding groove (40).…”
mentioning
confidence: 99%
“…Cytochrome c then induces the formation of a so-called apoptosome complex and subsequent activation of caspases (13). MCMV inhibits the intrinsic apoptosis pathway at mitochondria with two separate viral proteins: a BAX-specific inhibitor, encoded by open reading frame (ORF) m38.5 (14)(15)(16)(17), and a BAK-specific inhibitor, encoded by ORF m41.1 (18). The mitochondrion-localized m41.1 protein is expressed from the m41 locus and functions as viral inhibitor of BAK oligomerization (18).…”
mentioning
confidence: 99%